Two Children With Novel TRPC6 Spontaneous Missense Mutations and Atypical Phenotype: A Case Report and Literature Review - Wang, Meiqiu; Wang, Ren; He, Xu; Yu, Min; Xia, Zhengkun; Gao, Chunlin (Frontiers in Pediatrics, 2020)
Background: The phenotypes of TRPC6 mutations have been reported mainly in familial and sporadic focal segmental glomerulosclerosis (FSGS), which can occur in both adults and children. Herein, we report on two children with novel TRPC6 spontaneous missense mutations associated with immune complex-mediated glomerulonephritis and minor glomerular abnormality (MGA) that showed to be resistant to corticosteroids and other immunosuppressants. Case Presentation: A 9-year-old girl presented with steroid-resistant nephrotic syndrome (SRNS), while another 11-year-old boy developed proteinuria at 7 years old. Treatment with a variety of immunosuppressants had no effect, and the renal biopsy showed immune complex-mediated glomerulonephritis and MGA. No members of their family were clinically affected. Genetic testing was performed in the two patients, revealing two novel spontaneous missense mutations in TRPC6—N110S and P112R. The girl developed end-stage renal disease (ESRD) 5 months after onset while the boy continued to have sub-nephrotic range proteinuria and normal creatinine. Conclusions: Two novel TRPC6 mutations were associated with the atypical phenotype—immune complex-mediated glomerulonephritis and MGA, rather than FSGS as previously reported. Their rates of disease progression are different. Genetic testing is helpful to identify the etiology and avoid the side effects brought on by immunosuppressants.